Analisis Diftong Bahasa pada Masyarakat Penduduk Asli Flores Manggarai - Aldo, Albinus Halu; Baroroh, Hilma Erfiani (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The Flores Manggarai language is the first language used by the people of Flores Manggarai as their mother tongue. The Flores Manggarai language is also used as a language of daily communication both within the family and in the surrounding community. In West Flores there are three districts that use almost the same variety of language, namely West Manggarai, Central Manggarai and East Manggarai districts. These three districts have one language variety with several dialect variations. The Flores Manggarai language has unique grammatical characteristics that need to be studied, one of which is the use of diphthongs in the Flores Manggarai language. Diphthongs are two vowels that coincide and are read as one unit. Manggarai language is a language that generally often uses four diphthongs, namely /ai/, /au/, /ei/ and /oe/. The research location is located in Munting Village, South Lembor subdistrict, West Manggarai Regency. The data sources are oral and written data. Based on the research results, the word classes that contain diphthongs in the Manggarai language are verbs, nouns, adjectives, adverbs and task words.